Freedom's Empire : Race and the Rise of the Novel in Atlantic Modernity, 1640-1940 - Doyle, Laura (Laura Anne) (Book collections on Project MUSE., 2008)
A sweeping argument that from the mid-seventeenth century until the mid-twentieth, the English-language novel encoded ideas equating race with liberty.